Signal design and performance analysis for LEO high dynamic navigation application - Wang, Lei; Che, Jibin; Chen, Haoyan (Journal of navigation, 2023)
With the development of GNSS (Global Navigation Satellite System), LEO (Low Earth Orbit) systems are adopted to enhance the system performance of GNSS. The signal Doppler of the LEO satellite is seven to nine times that of GNSS signals, which benefits positioning performance but leads to high acquisition complexity. This paper proposes the combination of a CSS (Chirp Spread Spectrum) marker and the main body of traditional modulation methods for high dynamic application. The acquisition calculation complexity and mean acquisition time of the proposed signal are analysed and compared with the traditional signal. The result shows that the acquisition calculation complexity is just 26 % of the traditional signal under the parameters considered and the mean acquisition time of the proposed signal is also lower than the traditional signal. Hence, the proposed signal is able to decrease the mean acquisition time of the receiver under the constraint of calculation complexity and should be adopted for LEO high dynamic application.